The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/6568208
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Swelling‐Compression Characteristics of Clays in Yichang, China

Abstract: Expansive soil has been studied for eighty decades because it is prone to cause geotechnical engineering accidents. The results of the moisture content effects on the expansive pressure were not consistent in the literatures. In this paper, swelling deformation and pressure tests were conducted to clarify the effects of the initial water content on the swelling properties. The relation of expansive stress and initial moisture content was accurately described with a Gaussian distribution, unlike in the previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…However, on the wet side of OMC, the orientation of soil particles is much higher than that of the dry side, and therefore, the quantity of face-to-face contact also increases. As shown in Figure 16(a), the ∆P/P 0 value initially increased with increasing water content up to the optimum content range which is in good agreement with previous studies [61]. According to the earlier explanations, the reason for this can be attributed to the state of particle focculation with the edge-to-face contact and large voids between particles.…”
Section: Comparison Of the Efect Of Initial Water Content And Bofs St...supporting
confidence: 90%
“…However, on the wet side of OMC, the orientation of soil particles is much higher than that of the dry side, and therefore, the quantity of face-to-face contact also increases. As shown in Figure 16(a), the ∆P/P 0 value initially increased with increasing water content up to the optimum content range which is in good agreement with previous studies [61]. According to the earlier explanations, the reason for this can be attributed to the state of particle focculation with the edge-to-face contact and large voids between particles.…”
Section: Comparison Of the Efect Of Initial Water Content And Bofs St...supporting
confidence: 90%
“…The lower swelling stress values were noted at the wet side of the optimum as the dry density increases. The results concord with the outcome of the investigation conducted by [32] on the swelling pressure and meso-mechanism of Gaussian distribution under constant volume conditions, which revealed that the relation of expansive stress and initial moisture content depends on the change in the microstructure with diverse moisture contents. In addition, dry density and vertical stress influence expansive properties were also correlated with swelling stress.…”
Section: Swelling Stress -Gravimetric Moisture Content Relationshipsupporting
confidence: 77%
“…group index results. Accordingly, soils found in the study area are bad to medium subgrade category, which need different thickness of capping layer for pavement construction (Changxi et al , 2019 and Han et al , 2020).…”
Section: Resultsmentioning
confidence: 98%